2013
DOI: 10.1039/c2cc37904j
|View full text |Cite
|
Sign up to set email alerts
|

Isolated facial and meridional tris(bipyridine)Ru(ii) for STM studies on Au(111)

Abstract: Tripodal facial and meridional Ru(II) complexes comprising three conjugated legs with acetyl-protected thiol end groups are designed, synthesized and isolated for investigation on a gold surface. Preliminary ultrahigh vacuum scanning tunnelling microscopy (UHV STM) measurements of a monolayer of facial isomer deposited on Au(111) are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Synthesis and Main Characterizations of A and B (4-(N,N-dibutylamino)-4 0 -(5-ethynyl-2; 2 0 -bipyridine) (A): 5-(ethynyl)-2; 2 0 -bipyridine (100 mg, 0.55 mmol) [10] and 4-N-dibutylamino,4 0 -iodoazobenzene (0.55 mmol) [11] were dissolved in 30 mL of freshly distillated triethylamine, under argon. CuI (10 mg, 0.053 mmol) and PdPPh 3 2 Cl 2 (17 mg, 0.027 mmol) were added to the mixture.…”
Section: Methodsmentioning
confidence: 99%
“…Synthesis and Main Characterizations of A and B (4-(N,N-dibutylamino)-4 0 -(5-ethynyl-2; 2 0 -bipyridine) (A): 5-(ethynyl)-2; 2 0 -bipyridine (100 mg, 0.55 mmol) [10] and 4-N-dibutylamino,4 0 -iodoazobenzene (0.55 mmol) [11] were dissolved in 30 mL of freshly distillated triethylamine, under argon. CuI (10 mg, 0.053 mmol) and PdPPh 3 2 Cl 2 (17 mg, 0.027 mmol) were added to the mixture.…”
Section: Methodsmentioning
confidence: 99%
“…[27,28] Structures tabilization by Vand er Waals forcesi nm onolayers,a nd efficient packing in SAMs,h ave been reported for backbones consisting of C 3 tetrahedral symmetric units equipped with Si or Cc ores. [13,15,29] Our initial attempts toward tripodal modelc ompounds were based on coordinationc omplexes comprising both neutral M III complexes [30,31] and charged tris(bipyridine)-Ru II derivatives, [32] but our recentm olecular designscomprise purely organic scaffolds such as 9,9'-spirobifluorenes. [33] Active-tail groups have been introduced to demonstrate the presenceo ftripodalm olecules on electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Our initial attempts toward tripodal model compounds were based on coordination complexes comprising both neutral M III complexes and charged tris(bipyridine)‐Ru II derivatives, but our recent molecular designs comprise purely organic scaffolds such as 9,9′‐spirobifluorenes …”
Section: Introductionmentioning
confidence: 99%
“…PXRD analysis indicated that the crystal structure of the framework was maintained after the impregnation process (Fig. [24][25][26][27] The Li + ion conductivity of 3a, 3b and 3c was measured on pellets by ac impedance spectroscopy (Fig. The presence of solvated Li + ions inside the channels of porous CB [6] crystals was further corroborated using FT-IR spectroscopy.…”
mentioning
confidence: 89%